Improvement of Warehouse Facility Layout Using Dedicated and Class-based Storage Methods at PT Mitra Sarana Mahadana - Aditya Prathama (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2023)
PT Mitra Sarana Mahadana is a company engaged in the sale of PVC ceilings, PVC ceiling trim, and hollows. However, the products stored at this company are stored randomly, causing product damage when product pick-up is carried out. In addition, this random placement also causes a long search time to find a particular product so that time causes product retrieval to be inefficient and product damage causes storage to be ineffective. Therefore, improvements are needed using dedicated storage methods, class-based storage, and proposed improvements simulated using Arena. This study resulted in a conclusion in the form of a dedicated storage method succeeded in reducing the travel distance by 46.56% from the actual distance of 9,056.57 meters to 4,840.05 meters. From the simulation results, it was found that the dedicated storage method succeeded in reducing the product transfer process time by 79.85% from the actual time of 130 seconds to the proposed condition time of 26.2 seconds.